Pathologic Validation of Endoscopic Ablative Therapy for Gastric Epithelial Neoplasia: A Randomized Controlled Trial - Cheal Wung Huh; Jiyoung Kim; Byung-Wook Kim; Joon Sung Kim (Turkish Journal of Gastroenterology, 2021)
Background: The effectiveness of endoscopic ablative therapy such as monopolar coagulation (MC) or argon plasma coagulation (APC) have not been validated histologically. The aim of this study was the histologic validation of endoscopic ablative therapy for gastric epithelial neoplasia. Methods: We designed a prospective randomized controlled trial involving patients with gastric low-grade dysplasia. Patients were randomly assigned to either the APC or the MC group. Endoscopic ablative therapy was followed by endoscopic submucosal dissection (ESD) for histologic evaluation. The main outcome was histologic completeness of endoscopic ablative therapy. Results: Sixty-eight patients were recruited, of whom 34 patients underwent APC and 34 patients underwent MC followed by ESD. The APC group showed significantly higher complete eradication rate compared to the MC group (55.9% vs. 11.8%, P < .001). APC was the only significant predictor of histologic complete eradication in multivariate analysis (OR: 7.66; 95% CI: 2.139-27.448). No adverse events related to the procedure occurred in either group. Conclusions: Although APC is a more effective treatment option than MC in the management of gastric epithelial neoplasia, the effectiveness of both methods was limited in eradicating gastric epithelial neoplasia completely. Therefore, endoscopic resection should be a first option for treatment of gastric epithelial neoplasia until the optimal method is established with further studies. Cite this article as: Wung Huh C, Kim J, Kim B, Sung Kim J. Pathologic validation of endoscopic ablative therapy for gastric epithelial neoplasia: a randomized controlled trial. Turk J Gastroenterol. 2021;32(12):1029-1037.